Educational Issues in the Views of Eastern Thinkers - Khalilov, Farhod Furqat-ugli (Universitas Muhammadiyah Sidoarjo, 2022)
This thesis examines the thinkers of the East and their rich scientific and educational heritage. The thesis provides a brief overview of the modesty of some scientists and their activities.